ANALISIS PENERIMAAN RETRIBUSI PASAR TRADISIONAL KOTA PONTIANAK - B21110046, MARGIUS (Jurnal Curvanomic, 2015)
The objective of this study was to investigation income of Cempaka traditional market in Pontianak city. The study employed descriptive method with primary and secondary data and the data wasÂ  analyzed with level of effectiveness . Fidings indicated that the income of Cempaka traditional market was effective with level of effectiveness amounted 92,54 %.Â  Other factors that had significant influences on the retribution income of Cempaka traditional marketwere number of stalls, empty lane, attitude of market officers,and tariff. Keywords: level of effectiveness, number of stalls, empty lane, attitude of market officers, and tariff